New criminalization forms under the United Nations Convention against Corruption for the year 2003 - the crime of bribery in the private sector as a model (Journal of Human Sciences, 2022)
Corruption today is considered a very important topic as it still raises a lot of controversy regarding how to confront it and reduce its effects, which requires keeping pace with the development, diversity and renewal in its forms at the national and international levels. This is done by criminalizing its various acts and its various forms, so that it is not limited to acts of corruption that occur by the public employee, but also forms of corruption committed within the framework of the activity of the private sector, including the crime of bribery in the private sector. After Libya ratified the United Nations Convention against Corruption for the year 2003 under Law No. 10 of 2005, which included recent forms of corruption in order to suppress it and limit its effects, which constitutes an obstacle to development and development and a waste of society’s capabilities, including the crime of bribery in the private sector, as it is an effective partner in Economic development, which requires purification and careful control of its activity. The Convention has obligated the states party to it to stipulate in their national laws its criminalization and to develop their legislation in line with the provisions of the Convention. Therefore, we will discuss in this research the legal treatment of the crime of bribery in the private sector as one of the forms of corruption in the 2003 United Nations Convention, by clarifying the nature of bribery and the scope of its criminalization in a first section. We analyzed its legal framework in the Libyan Penal Code, the United Nations Convention against Corruption and the mechanisms of international cooperation to combat it, and we reached some results and recommendations, the most important of which are. The crime of ordinary bribery is shared with bribery in the private sector in most of its aspects, with the exception of the two categories of the briber, who must be a public employee in the ordinary crime of bribery and an employee or private employee in private projects in this crime. The Libyan Penal Code did not address all forms of the crime of bribery in the private sector, although Libya ratified the Convention on Combating Corruption, and therefore has a legal obligation under it, to take legal measures to criminalize bribery in the private sector in all its forms. The necessity of involving the private sector in combating corruption through corporate corporate governance as an anti-corruption mechanism.